2021
DOI: 10.20944/preprints202109.0310.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interaction Between Grasses and <em>Epichloe</em> Endophytes and Its Significance to Biotic and Abiotic Stress Tolerance and the Rhi-Zosphere

Abstract: Cool-season grasses are the most common forage types in livestock operations and amenities. Several of the cool-season grasses establish mutualistic associations with an endophytic fungus of the Epichloe genus. The grasses and endophytic fungi have evolved over a long period of time to form host-fungus specific relationships that confer protection for the grass against various stressors in exchange for housing and nutrients to the fungus. This review provides an overview of the mechanisms by which Epichloe end… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 153 publications
(205 reference statements)
0
1
0
Order By: Relevance
“…Previous studies revealed that rhizosphere microbial communities are susceptible to changes in environmental and plant varieties (Lee et al, 2021;Munoz et al, 2021). However, it is still unclear how tea varieties and soil characteristics affect the structure and functions in rhizosphere bacterial and fungal communities, and the information on beneficial microbial groups is largely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that rhizosphere microbial communities are susceptible to changes in environmental and plant varieties (Lee et al, 2021;Munoz et al, 2021). However, it is still unclear how tea varieties and soil characteristics affect the structure and functions in rhizosphere bacterial and fungal communities, and the information on beneficial microbial groups is largely lacking.…”
Section: Introductionmentioning
confidence: 99%